2019
DOI: 10.1186/s40248-019-0172-9
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and comorbidities: a dangerous liaison

Abstract: Obstructive sleep apnea (OSA) is a highly prevalent disease, and is traditionally associated with increased cardiovascular risk. The role of comorbidities in OSA patients has emerged recently, and new conditions significantly associated with OSA are increasingly reported. A high comorbidity burden worsens prognosis, but some data suggest that CPAP might be protective especially in patients with comorbidities. Aim of this narrative review is to provide an update on recent studies, with special attention to card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
132
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(140 citation statements)
references
References 179 publications
(162 reference statements)
5
132
1
2
Order By: Relevance
“…These disruptions may impair subjects' abilities to reach the desired deep, restful phases of sleep, with subjects likely feeling sleepy during waking hours. Subjects with OSA may be unaware that their sleep was interrupted, with many of these subjects thinking that they slept well throughout the night [3].…”
Section: Introductionmentioning
confidence: 99%
“…These disruptions may impair subjects' abilities to reach the desired deep, restful phases of sleep, with subjects likely feeling sleepy during waking hours. Subjects with OSA may be unaware that their sleep was interrupted, with many of these subjects thinking that they slept well throughout the night [3].…”
Section: Introductionmentioning
confidence: 99%
“…A high prevalence of comorbidities in seen in OSA patients (17). There are specific patterns, with men more often affected by diabetes and ischemic hearts disease and women by hypertension and depression (18,19).…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Recent studies have also shown that OSA is part of the MetS. The intermittent hypoxia and the sleep loss or fragmentation are involved in the pathogenesis of insulin resistance (17). In these conditions, OSA treatment with sufficient adherence (at least 4 hours/night) is required besides the implementation of lifestyle interventions and weight loss programs (22).…”
Section: Comorbiditiesmentioning
confidence: 99%
See 2 more Smart Citations